(untitled) (Fiep Bulletin - online, 2012)
This qualitative study aimed to investigate how the authors of the leisure area discuss the professional training and the factors that hinder the performance in this scenario. It is a literature search that investigated four articles of more scientific evidence on the subject in question. Most publications were found in Liecre magazine, from 1998 to 2009, being great part of authors from physical education field. The analysis of data was based on the factors that hinder the professional training within the leisure from fragments found in the texts selected for analysis. It highlighted the following categories: a) historical tradition; b) misunderstanding of activity in the area c) multi-faceted features of market activity; d) a non-disciplinary character of thematic e) devaluation of the profession; f) the professional profile required. Other initiatives of studies on professional training in the leisure are suggested generating a paradigm shift in this area.